Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

solve the following:

2(x + 3) = x - 4

4(5x - 2) = 2(9x + 3)


Sagot :

Step-by-step Solution(s):

Solving for 2(x + 3) = x - 4.

  • 2(x + 3) = x - 4
  • => 2x + 6 = x - 4
  • => 2x - x = -6 - 4
  • => x = -10

Solving for 4(5x - 2) = 2(9x + 3)

  • 4(5x - 2) = 2(9x + 3)
  • => 20x - 8 = 18x + 6
  • => 20x - 18x = 8 + 6
  • => 2x = 14
  • => x = 7

Hoped this helped!